Enterologic and gynaecologic complications of ovariohysterectomy in the bitch (2012)
The enterologic and gynaecologic associated complications post ovariohysterectomy (OVH) in bitches were evaluated. Medical records of 53 bitches with mean body weight of 15.2kg presented at the Veterinary Teaching Hospital (VTH), University of Ibadan between 1990-2010 were reviewed. Enterologic complications after OVH were observed in 11 (20.7%) of the cases studied. These include: Chronic vomiting 9 (81.8%), weight loss 9 (81.8%), anorexia, 8 (72.7%), diarrhea, 6 (54.5%) and pyrexia, 5(54.5%). Nine of the 11 dogs (81.8%) had extensive intestinal and uterine stump adhension. Gynaecologic complications 0bserve in 23 (43.3%) of the 53 bitches included vulva discharge 21(91.3%), incomplete extirpation of the ovaries 14(60.8%), recurrent estrus 9(39.1%), pseudopregnacy 8(34.7%), inflammation of the uterine cervical tissue and stump 4(17.4%) and non-resorbable ligature 3(13.0%). The study shows that enterologic and gynaecologic complications occur following OVH in bitches and strongly advice that bitches with gastrointestinal symptoms following OVH should be suspected of intestinal adhesions and incarcerations